DAMPAK MEDIA SOSIAL TERHADAP PURCHASE INTENTION ITEM VIRTUAL PADA GAME ONLINE GENSHIN IMPACT - Suprehatin Siti Romelah (POLITEKNIK LP3I JAKARTA, 2024)
Genshin Impact quickly rose to fame as one of the most played mobile games in the world after gaining widespread recognition. Many gamers, especially those who are truly dedicated to gaming, have engaged in this practice of purchasing virtual goods. The main objective of this research is to measure the impact of Twitter as a social media platform on interest in purchasing in-game products in the Genshin Impact video game. Using IBM SPSS version 26, this research uses quantitative analysis tools. One hundred people participated in this research by filling out a questionnaire sent to them via Direct Message (DM) by the official Twitter account @GenshinImpact. The sampling technique used was purposive sampling, and the number of samples was 100. A series of tests, including validity and reliability tests as well as statistical analysis and coefficient of determination, were used to analyze the data. This research found that the intention to purchase virtual goods (Y) was influenced positively and significantly by the social media variable (X). Key words: Media Social, Purchase Intention, Item Virtual